"We live a life in periods" - Perceptions of mobility and becoming an expat spouse - Büchele, Julia (Migration Letters, 2018)
Deploying organizations strongly support their employees’ relocation with their spouses and children under the premise that families guarantee a social and practical support system (Kraimer et al. 2016). Expat spouses I have interviewed in the course of my qualitative data collection were sure that their migration experience differed significantly from their employed spouses. While for themselves relocation was a (repeated) interruption of the “normal pace of life”, they assumed that their husbands were provided with a “ready-made life” because they started work right away and were thus integrated in a local social setting. This paper explorse different perceptions of expat spouses’ mobility and argues that expat spouses learn to be expat spouses through repeated relocations and "mobility work" ( Mense-Petermann and Spiegel 2016).